Structural basis for inhibition of the RNA-dependent RNA polymerase from SARS-CoV-2 by remdesivir - Yin, Wanchao; Mao, Chunyou; Luan, Xiaodong; Shen, Dan-Dan; Shen, Qingya; Su, Haixia; Wang, Xiaoxi; Zhou, Fulai; Zhao, Wenfeng; Gao, Minqi; Chang, Shenghai; Xie, Yuan-Chao; et al. (Science (American Association for the Advancement of Science), 2020)
Understanding the inner workings of the virus that causes coronavirus disease 2019 (COVID-19) may help us to disrupt it. Yin et al. focused on the viral polymerase essential for replicating viral RNA. They determined a structure of the polymerase bound to RNA and to the drug remdesivir. Remdesivir mimics an RNA nucleotide building block and is covalently linked to the replicating RNA, which blocks further synthesis of RNA. The structure provides a template for designing improved therapeutics against the viral polymerase. Science , this issue p. 1499 Cryo-EM structures show how the drug remdesivir binds to the RNA polymerase to block RNA elongation. The pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a global crisis. Replication of SARS-CoV-2 requires the viral RNA-dependent RNA polymerase (RdRp) enzyme, a target of the antiviral drug remdesivir. Here we report the cryo–electron microscopy structure of the SARS-CoV-2 RdRp, both in the apo form at 2.8-angstrom resolution and in complex with a 50-base template-primer RNA and remdesivir at 2.5-angstrom resolution. The complex structure reveals that the partial double-stranded RNA template is inserted into the central channel of the RdRp, where remdesivir is covalently incorporated into the primer strand at the first replicated base pair, and terminates chain elongation. Our structures provide insights into the mechanism of viral RNA replication and a rational template for drug design to combat the viral infection.